Experience of Kazakhstan diplomats participation in the UN General Assembly activity (International relations and international law Journal, 2016)
This article discusses the experience of Kazakh diplomats attending the UN General Assembly working session in different years. Being a member of the Soviet delegation, representatives of Kazakhstan adequately demonstrated the knowledge and skills of diplomacy.Their abilities have been assessed by the management of the USSR Foreign Ministry. After independence participation of the Kazakh diplomats in the work of this international organization was carried out in the framework of the activity of the Permanent Representative of Kazakhstan to the United Nations. The article highlighted the contribution of the first representatives of Kazakhstan to the United Nations, reviewed the initiatives of the state in the implementation of preventive diplomacy. Particular attention is paid to the role of the First President of the Republic of Kazakhstan in the development of multilateral diplomacy.
Keywords: United Nations; General Assambly; Kazakh diplomats; the Republic of Kazakhstan; the Permanent Representative of Kazakhstan